Evaluation of Waste Management Policy in Malang City - Anisykurlillah, Rosyidatuzzahro; Sampe, Stefanus; Bataha, Katerina (Jayapangus Press, 2024)
Climate change is a challenge faced by various countries, including Indonesia, and makes it part of the Sustainable Development Goals (SDGs) agenda. This environmental phenomenon is influenced by various sectors, including waste, whose management in Indonesia has not been optimal. Malang City is one of the cities with the highest waste generation in East Java. Regarding waste management in Malang City, the City Government has issued the latest policy, namely Malang City Regional Regulation (Perda) No. 7 of 2021 concerning Waste Management. This regional regulation replaces Regional Regulation No. 10 of 2010 concerning Waste Management, which is no longer valid. This study aims to describe and analyze the evaluation of waste management policies in Malang City. The type of research used is descriptive with a qualitative approach. The evaluation method is the Context, Input, Process, and Product (CIPP). The data analysis technique used in this research is the interactive model analysis of Miles, Huberman, and Saldana. If we look at the evaluation results using the CIPP method, we find obstacles that must be resolved for the success of waste management policies in Malang City. These obstacles include facilities and infrastructure for waste management in Malang City, which still need to be met, the lack of community role in the program for sorting waste from the source, and waste management operations, which require large budget allocations.